Organizational Problems of Machine-Building Enterprises in the Context of Small-Scale Production - Tipner Lyudmila (EDP Sciences, 2021)
The need to increase labour productivity and improve the competitiveness of engineering products, as well as to increase high-tech exports, are urgent tasks for the development of industry in the Russian Federation. The creation of competitive products implies flexibility in the approach to the consumer, which leads to an increase in the share of enterprises operating in conditions of small-scale production. The purpose of this study is to assess the reserves of productivity growth at machine-building enterprises of small-scale and unit-type production in the Ural region. Research has shown that organizational factors, such as the automation of production preparation processes, the use of photo-timing studies in the conditions of small-scale production, have a significant impact on labour productivity. In this case, the solution of organizational problems helps to create informational database for introduction at the enterprises of mechanical engineering complex life cycle management of products (the PLM).